2010
DOI: 10.5424/fs/2010191-01170
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal status of a mature productive black truffle plantation

Abstract: The black truffle (Tuber melanosporum Vittad.) is an hypogeous ascomycete endemic to Mediterranean calcareous soils in southern Europe which is found in symbiotic association with roots of deciduous trees, mostly oaks (Quercus spp.) and hazelnut trees (Corylus avellana L.) (Delmas, 1978;Olivier et al., 2002).Black truffle is a first-class product, the production of which is clearly standstill after the sudden fall in the middle of 20 th century. In the f irst half of this AbstractThe truffle-plantation «Los Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 19 publications
(17 reference statements)
1
3
1
Order By: Relevance
“…Our data confirmed that the genus Tomentella is widespread and an important component in orchards with Tuber spp. (Murat et al, 2005;Pruett et al, 2008;Águeda et al, 2010;Iotti et al, 2010;Benucci et al, 2011;Belfiori et al, 2012;Leonardi et al, 2013). In agreement with Donnini et al (2008), who reported the frequent fruiting of Tricholoma species in truff ières, Tricholoma terreum was also found to be more abundant than Tuber aestivum in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data confirmed that the genus Tomentella is widespread and an important component in orchards with Tuber spp. (Murat et al, 2005;Pruett et al, 2008;Águeda et al, 2010;Iotti et al, 2010;Benucci et al, 2011;Belfiori et al, 2012;Leonardi et al, 2013). In agreement with Donnini et al (2008), who reported the frequent fruiting of Tricholoma species in truff ières, Tricholoma terreum was also found to be more abundant than Tuber aestivum in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Ectomycorrhizal communities on root tips in natural and cultivated truffières have been amply investigated (Donnini and Bencivenga, 1995;Donnini et al, 1999;Murat et al, 2005;Baciarelli Falini et al, 2006;Pruett et al, 2008;Águeda et al, 2010;González-Armada et al, 2010;Iotti et al, 2010;Benucci et al, 2011;Garcia-Barreda and Reyna, 2012;Leonardi et al, 2013). However, according to Tóth and Barta (2010) very few studies have simulEctomycorrhizal communities and truffle productivity 335 taneously analyzed fungal species both above and below ground in relation to varying environmental factors or with the aim of determining their suitability as indicators of environmental change.…”
Section: Discussionmentioning
confidence: 99%
“…Since the EM fungi differ in their preference for soil depth (Courty et al 2008), the EM community is likely to differ from that in wild truffières. In addition, the abundance of T. melanosporum ectomycorrhizas in our study is lower than generally reported in truffle plantations (which are usually established with nursery-inoculated seedlings on agricultural soils), and the richness of soil-borne EM fungi is higher (Sánchez-Durán et al 2009;Águeda et al, 2010). Further study in nonproductive trees is necessary to elucidate its potential role in the renovation of truffle production.…”
Section: Temporal Evolution After the Canopy Openingcontrasting
confidence: 56%
“…). Heterogeneous distributions of vegetative T. melanosporum structures were observed in previous studies comparing productive and non‐productive truffle grounds (Águeda et al ., ; Parladé et al ., ), and the biomass of mycelium in soils may vary significantly between seasons, as reported for some ECM fungal species (De la Varga et al ., ). The significant finding of our study was that some samples from immature and productive brûlés did contain high levels of truffle mycelium.…”
Section: Discussionmentioning
confidence: 99%
“…In published work dealing with the particular case of T. melanosporum truffle grounds, all vegetative parts, the ECM tips and the mycelium are generally reported to be more abundant in productive stands than non‐productive ones (Águeda et al ., ; Zampieri et al ., ; Parladé et al ., ), with few exceptions (Suz et al ., ). There is no clear threshold indicating the onset of ascocarp production (De la Varga et al ., ; Parladé et al ., ) and the presence of ECM tips can even be maintained over several decades in plantations without production (Águeda et al ., ). Similarly, the distribution of ECM tips poorly reflects the production of T. magnatum (Murat et al ., ; Leonardi et al ., ).…”
Section: Discussionmentioning
confidence: 99%